2016
DOI: 10.1111/1750-3841.13557
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Superheated Steam Roasting and Water Activity Control as Oxidation Mitigation Methods on Physicochemical Properties, Lipid Oxidation, and Free Fatty Acids Compositions of Roasted Rice

Abstract: The feasibility of using superheated steam roasting and wetting to control the water activity in an optimal range to mitigate oxidation of roasted rice was evaluated. Changes in the bed temperature as well as rice kernel moisture content, water activity, and color were monitored during fluidized bed roasting with superheated steam and hot air at 170, 190, and 210 °C. Air-roasted rice was rewetted to raise its water activity to 0.30 to 0.35. All the samples were analyzed for the total oil content, peroxide valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…is was in accordance with a study on rainbow trout which showed lower TBARS values in essential oil-treated rainbow trout compared with the control group [37]. Lower TBARS values in rice samples roasted by superheated steam than the hot air were reported by Yodkaew et al [40]. Another experiment that compared superheated steam treatment and conventional pan-frying treatment on pork bundle conducted by Huang et al [41] showed suppressed content of peroxide values (POV), TBARS, and volatile compounds.…”
Section: Discussionsupporting
confidence: 92%
“…is was in accordance with a study on rainbow trout which showed lower TBARS values in essential oil-treated rainbow trout compared with the control group [37]. Lower TBARS values in rice samples roasted by superheated steam than the hot air were reported by Yodkaew et al [40]. Another experiment that compared superheated steam treatment and conventional pan-frying treatment on pork bundle conducted by Huang et al [41] showed suppressed content of peroxide values (POV), TBARS, and volatile compounds.…”
Section: Discussionsupporting
confidence: 92%
“…For more information on the fluidized bed roasting system set‐up, the reader is referred to Yodkaew et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…Because of the limitations of hot air as the roasting medium, superheated steam has been proposed as an alternative roasting medium and has been applied to a variety of products, including cocoa beans, peanut, and rice (Idrus & Yang, ; Yodkaew, Chindapan, & Devahastin, ; Zzaman & Yang, ). In the case of coffee beans, superheated steam roasting at appropriate conditions has shown to help increase the extraction efficiency, decrease the losses of dry solids and desirable aroma compounds as well as remove the naturally occurring undesirable flavor (that is, cereal and musty flavor) of Robusta beans (Maki & Haruyama, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination, another food processing technique of whole grains, increases healthy functional components, but, results in an unsavoury flavour profile. Further, another study showed that when water activity is not controlled during superheated steaming, a technique that can be utilised to roast rice, there is a significant increase in peroxide value and TBA of rice (Yodkaew et al, 2017). Fortification of cereal products can also reduce their antioxidant components.…”
Section: Food Processing and Lipid Oxidationmentioning
confidence: 99%